KREDIT (AT-TAQHSITH) DALAM DISKURSUS HADIS NABI MUHAMMAD SAW - Taufiq Sanusi Baco (El-Iqthisadi, 2020)
AbstractCredit in conventional banking is haram because it uses a refined usury system called interest, both credit is productive, especially consumptive based on the Alquran and the hadith of the prophet about usury that Abbas, his uncle, saw. Credit in Syari'ah banking is allowed because credit at Bank Syari'ah is transferred to mudharabah for the productive and ba'i bi at-taqshid for the consumptive based on the hadith of the Prophet Muhammad and the opinion of the scholars. Basically the whole concept of mu'amalah is permissible as long as it doesn’t contradict the principles of the Alquran and sunnah such as the ushul kaedah which means: "the origin (law) mu'amalah is permissible as long as there is no argument against it". In the hadith we don’t find that credit is sacrificed, but we will find a form of credit that is almost the same (if it is applied) to credit carried out by merchants who use the usury system, namely debt payments with credit within the specified time with excessive profit (usury fadl). Keywords: Credit, Discourse, Hadith, Riba. AbstrakKredit pada perbankan Konvensional adalah haram karena memakai sistem riba yang diperhalus dengan sebutan bunga, baik kredit itu bersifat produtik lebih-lebih yang bersifat konsumtif berdasarkan Alqur’an dan hadis nabi tentang riba yang pernah dilakukan Abbas, paman beliau saw. Kredit pada perbankan Syari’ah dibolehkan karena kredit pada Bank Syari’ah dialihkan pada sifat mudharabah bagi yang produktif dan dengan sifat ba’i bi at-taqshid bagi yang konsumtif berdasarkan hadis nabi Muhammad saw dan pendapat ulama. Pada dasarnya seluruh konsep mu’amalah adalah boleh selama tidak bertentangan dengan prinsip-prinsip Alqur’an dan sunah seperti kaedah ushul yang artinya: “asal (hukum) mu’amalah adalah boleh selama tidak ada dalil yang melarangnya”. Dalam hadis kita tidak menemui tentang kredit diperbankan, akan tetapi kita akan menemui bentuk kredit yang hampir sama (jika diqiaskan) dengan kredit yang dilakukan oleh pedagang-pedagang yang menggunakan sistem riba yaitu pembayaran hutang dengan kredit dalam waktu yang ditentukan dengan keuntungan yang berlebih-lebihan (riba fadl).Kata Kunci : Diskursus, Hadis, Kredit, Riba.